Analisis Hubungan Antara Kepuasan Kerja dan Loyalitas Karyawan pada Lingkungan Industri - Salwa Zahira Salsabilah (JURAL RISET RUMPUN ILMU TEKNIK, 2025)
This study aims to analyze the relationship between job satisfaction and employee loyalty in an industrial environment. Job satisfaction is measured based on several factors, such as compensation, work environment, opportunities for development, and recognition of performance, all of which have a significant effect on employee loyalty. The method used is a literature study with a quantitative descriptive approach, reviewing various theories and previous research findings related to the two variables. The results of the study indicate that high job satisfaction is directly related to higher levels of employee loyalty, which is reflected in positive attitudes towards the company, long-term commitment, and reduced turnover rates. Therefore, companies in the industrial sector are advised to focus on improving employee job satisfaction in order to strengthen loyalty and support the long-term success of the organization.